A new Asphondylia species (Diptera: Cecidomyiidae) and a eulophid wasp (Hymenoptera) inducing similar galls on leaf buds of Schoepfia jasminodora (Schoepfiaceae), with reference to their ecological traits and a description of the new gall midge. Issue 3 (16th May 2018) - Elsayed, Ayman Khamis; Matsuo, Kazunori; Kim, Wanggyu; Uechi, Nami; Yukawa, Junichi; Gyoutoku, Naohisa; Tokuda, Makoto
Abstract : We report that Asphondylia tojoi Elsayed & Tokuda, sp. nov. (Diptera: Cecidomyiidae) and Ceratoneura sp. (Hymenoptera: Eulophidae) induce similarly shaped galls on leaf buds of Schoepfia jasminodora Sieb. et Zucc. (Schoepfiaceae). We describe the gall midge species as new to science and report a phylogenetic analysis for known Japanese Asphondylia species. In addition, we describe life histories of the two species, based on monthly surveys during 2015–2017: A. tojoi represents the first example of a monophagous Asphondylia species with a multivoltine life history on a deciduous tree; and Ceratoneura sp. is probably a true gall inducer. Abstract: Different gall inducers belonging to distinct insect orders are rarely known to induce similarly shaped galls on the same host plant organs. We report that Asphondylia tojoi Elsayed & Tokuda sp. nov. (Diptera: Cecidomyiidae) and Ceratoneura sp. (Hymenoptera: Eulophidae) induce galls on leaf buds of Schoepfia jasminodora Sieb. et Zucc. (Schoepfiaceae). We describe the gall midge species as new to science and report a phylogenetic analysis for known Japanese Asphondylia species. We also describe life histories of the two species, based on monthly surveys during 2015–2017: although both species are multivoltine, A. tojoi overwinters as first instars in galls, whereas Ceratoneura sp. possibly does so as adults outside the galls. In addition, the internal structure of galls differed between the two species. Galls containing A. tojoi consist of a single chamber with inner walls clearly covered with whitish fungal mycelia after the gall midges develop into second instars. Those containing the Ceratoneura sp. have multiple chambers with hard black inner walls. Although some eulophids are known to be inquilines of galls induced by Asphondylia species, we consider that the Ceratoneura sp. is probably a true gall inducer because of the different gall structure and absence of fungal mycelia in their galls. This is the first report detailing the annual life history of a Ceratoneura species. Asphondylia tojoi represents the first example of monophagous Asphondylia species with a multivoltine life history on a deciduous tree.